Structure of lipid multilayers via drop casting of aqueous liposome dispersions. Issue 17 (24th March 2016) - Sironi, Beatrice; Snow, Tim; Redeker, Christian; Slastanova, Anna; Bikondoa, Oier; Arnold, Thomas; Klein, Jacob; Briscoe, Wuge H.
Abstract : Liposomes serve as a lipid delivery matrix and a structural precursor, facilitating solid-supported lipid multilayer formation via simple drop casting. Abstract : Understanding the structure of solid supported lipid multilayers is crucial to their application as a platform for novel materials. Conventionally, they are prepared from drop casting or spin coating of lipids dissolved in organic solvents, and lipid multilayers prepared from aqueous media and their structural characterisation have not been reported previously, due to their extremely low lipid solubility ( i.e. ∼10 −9 M) in water. Herein, using X-ray reflectivity (XRR) facilitated by a "bending mica" method, we have studied the structural characteristics of dioleoylphosphatidylcholine (DOPC) multilayers prepared via drop casting aqueous small unilamellar and multilamellar vesicle or liposome ( i.e. SUV and MLV) dispersions on different surfaces, including mica, positively charged polyethylenimine (PEI) coated mica, and stearic trimethylammonium iodide (STAI) coated mica which exposes a monolayer of hydrocarbon tails. We suggest that DOPC liposomes served both as a delivery matrix where an appreciable lipid concentration in water (∼25 mg mL −1 or 14 mM) was feasible, and as a structural precursor where the lamellar structure was readily retained on the rupture of the vesicles at the solid surface upon solvent evaporation to facilitate rapid multilayer formation. We find that multilayers on mica from MLVs exhibited polymorphism, whereas the SUV multilayers were well ordered and showed stronger stability against water. The influence of substrate chemistry ( i.e. polymer coating, charge and hydrophobicity) on the multilayer structure is discussed in terms of lipid–substrate molecular interactions determining the bilayer packing proximal to the solid–liquid interface, which then had a templating effect on the structure of the bilayers distal from the interface, resulting in the overall different multilayer structural characteristics on different substrates. Such a fundamental understanding of the correlation between the physical parameters that characterise liposomes and substrate chemistry, and the structure of lipid multilayers underpins the potential development of a simple method via an aqueous liposome dispersion route for the inclusion of hydrophilic functional additives ( e.g. drugs or nanoparticles) into lipid multilayer based hybrid materials, where tailored structural characteristics are an important consideration.